The Fundamental Position Of Lex Posterior Derogat Legi Priori in the Conflict of Norms Against the Rights of Holders of The Right to Justice - Mesa Indra Naiborhu; Wagiman Wagiman (Publikasi Indonesia, 2024)
The principle as a fundamental rule is the background of the legal system, starting from the formulation and formation of laws and regulations to the enforcement of the regulations in question. Legal principles are a very important element in the formation of laws and regulations. Violation of norms shows a tendency to violate principles, and the elimination of norms will impact the tendency to eliminate principles. The methods used are the conceptual approach and the statute approach. The data sources used are secondary data that researchers can obtain from literature studies in the form of books, records, newspapers, journals, and other documents that can be used in this study. Secondary data consists of primary legal materials, secondary legal materials, and tertiary legal materials. Research results: (1) The position of the lex posterior derogat legi priori principle cannot be placed as a basis for overcoming the conflict of norms between UUK-PKPU and UUHT. (2) Resolution of norm conflicts between UUK-PKPU and UUHT can be done through a harmonisation approach of the two laws through the legislative process in the DPR. The bankruptcy process shows a conflict arising between UUK-PKPU and UUHT because the holder of the dependent right should still be authorised to exercise all his rights even though the grantor of the dependent right is declared bankrupt by article 21 of the Law. In contrast, Article 56 paragraph (1) suspends the rights of creditors of the holder of the 'dependent right'. To overcome the conflict of norms, it should be understood that the principle of lex posterior derogat legi priori means that the new norms/rules of law perfect the enforceability of the old norms/rules of law in the same legal regime